If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -1 = 4x + 7 Reorder the terms: -1 + 3s = 4x + 7 Reorder the terms: -1 + 3s = 7 + 4x Solving -1 + 3s = 7 + 4x Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3s = 7 + 1 + 4x Combine like terms: -1 + 1 = 0 0 + 3s = 7 + 1 + 4x 3s = 7 + 1 + 4x Combine like terms: 7 + 1 = 8 3s = 8 + 4x Divide each side by '3'. s = 2.666666667 + 1.333333333x Simplifying s = 2.666666667 + 1.333333333x
| -3(c-8)=24 | | 3(x+5)-6=27 | | -8-1x=1x-4x | | -5=3-(5-b) | | 4x^4=24x^2+108 | | 0.75x+3=15 | | 7x+21-5x=4x-15-3x | | 0.5(2a-4b)+0.3(a+b)= | | p/12-.6=3.472 | | (5x)(x+10)=0 | | 3x+6x=54x | | 40+14y=20-8y-6 | | 1+6c-7=-3 | | 8-b= | | 14y-14=7x+14 | | -12=6x-8x-14 | | (2x+1)(7x*9-9+3)+4-7=49 | | X+6x+49=5x+59 | | (n-8)(n-8)=169 | | c+d= | | x^2+11x-39=2x-3 | | .6(25k-7.5k)+9.5=20 | | 29-4y=2y-7 | | 14-5x=-56 | | x^2+36=40 | | (N-8)2=169 | | 5x-4=2x+2 | | -6j+5j-12=71-3*13 | | x^3=43 | | 18=-(k+3) | | 5+x=6-3+12 | | (1-2a)(3+5)-2=-10 |